2000
DOI: 10.1212/wnl.54.11.2166
|View full text |Cite
|
Sign up to set email alerts
|

Temporal lobectomy outcome in older versus younger adults

Abstract: A total of 340 patients age 50 years and older were compared with 30 patients younger than 50 years, all of whom had anterior temporal lobectomy for refractory epilepsy. Seizure outcome, neuropsychological test scores, and change in driving status were analyzed. Age and duration of epilepsy were related independently to outcome, but laterality of interictal sharp waves (an early epilepsy risk factor) and presence of tumor were not. Sixteen patients (52%) in the older group and 257 patients (75.6%) in the young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 5 publications
7
60
5
Order By: Relevance
“…Conversely, a Brazilian investigation reported no statistical difference of age at surgery with regard to postsurgical outcome after temporal lobectomy 22 . We did not observe a statistical difference regarding outcomes between patients younger and older than 50 years at the time of surgery (Table 5); the procedure proved to be safe and beneficial to both groups, which is in accordance with the literature 21 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Conversely, a Brazilian investigation reported no statistical difference of age at surgery with regard to postsurgical outcome after temporal lobectomy 22 . We did not observe a statistical difference regarding outcomes between patients younger and older than 50 years at the time of surgery (Table 5); the procedure proved to be safe and beneficial to both groups, which is in accordance with the literature 21 .…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, Sirven et al 21 studied a large number of patients undergoing temporal lobectomy and observed that patients younger than 50 years had a higher likelihood of seizure freedom compared with those older than 50 years, although the procedure was considered safe and beneficial in both groups. Conversely, a Brazilian investigation reported no statistical difference of age at surgery with regard to postsurgical outcome after temporal lobectomy 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sirven et al [20] compared postsurgical seizure outcome, neuropsychological test scoring and driving status in 30 patients aged 50 and older (median age 51.9) to 340 younger patients (median age 32.8). 53% of the older patients were seizure free as compared to 75% in the younger group.…”
Section: Discussionmentioning
confidence: 99%
“…However, few articles have reported encouraging results comparable to those in younger patients with refractory TLE [4,5,20]. There are only a few studies in older adults which evaluate postsurgical neurocognitive outcome.…”
Section: Introductionmentioning
confidence: 99%